Do bacterial and fungal communities assemble differently during primary succession?. Issue 2 (February 2014) - Schmidt, S. K.; Nemergut, D. R.; Darcy, J. L.; Lynch, R.
<x xml:space="preserve">Abstract</x> High‐throughput sequencing technologies are now allowing us to study patterns of community assembly for diverse microbial assemblages across environmental gradients and during succession. Here we discuss potential explanations for similarities and differences in bacterial and fungal community assembly patterns along a soil chronosequence in the foreland of a receding glacier. Although the data are not entirely conclusive, they do indicate that successional trajectories for bacteria and fungi may be quite different. Recent empirical and theoretical studies indicate that smaller microbes (like most bacteria) are less likely to be dispersal limited than are larger microbes – which could result in a more deterministic community assembly pattern for bacteria during primary succession. Many bacteria are also better adapted (than are fungi) to life in barren, early‐successional sediments in that some can fix nitrogen and carbon from the atmosphere – traits not possessed by any fungi. Other differences between bacteria and fungi are discussed, but it is apparent from this and other recent studies of microbial succession that we are a long way from understanding the mechanistic underpinnings of microbial community assembly during ecosystem succession. We especially need a better understanding of global and regional patterns of microbial dispersal and what environmental factors control the development of microbial communities in complex natural systems.